HUBUNGAN MOTIVASI BELAJAR DAN STATUS SOSIAL EKONOMI KELUARGA DENGAN HASIL BELAJAR MATA PELAJARAN TEKNOLOGI DASAR OTOMOTIF: Hubungan Motivasi Belajar Dan Status Sosial Ekonomi Keluarga Dengan Hasil Belajar Mata Pelajaran Teknologi Dasar Otomotif - gustama rahardi; setuju setuju; nurcholis arifin handoyono (JURNAL VOKASI DEWANTARA (JVD), 2022)
The aim of this study was to see if: (1) there is a significant positive relationship between learning motivation and basic car technology learning outcomes, and (2) there is a significant positive relationship between student learning outcomes and family socioeconomic status. (3) there is a significant positive relationship between learning motivation and family socioeconomic status with learning outcomes for basic car technology. Questionnaires and records were used to collect data. A questionnaire is used as a study tool. The data analysis methodology used inferential statistical analysis, the first and second hypothesis tests used partial correlation tests, and the third hypothesis test used two predictors' multiple regression. The analysis criteria tests, including the normality, linearity, and independence tests, were then conducted. The results show: (1) There is a significant positive relationship between the motivation to learn basic automotive technology and learning outcomes. (2) There is a significant positive relationship between family socioeconomic status and learning outcomes for basic car technology. (3) There is a significant positive relationship between learning motivation and family socioeconomic status with learning outcomes for basic car technology.